2022
DOI: 10.9734/ijecc/2022/v12i111375
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability and Interrelationship in Maize (Zea mays L.) Genotypes for Grain Yield and Yield Component Characters

Abstract: An experiment was conducted including 20 genotypes of maize during Kharif season of 2020-21. All characters under study showed highly significant variation. High values of genotypic and phenotypic coefficients of variation were observed for the characters like anthesis and silking interval, grain yield per plant, biological yield, number of grains per row, number of grain rows per cob, harvest index and ear height. Biological yield per plant, plant height, grain yield per plant, ear height and harvest index sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…High genetic advance for grain yield was also found by Sesay et al [14], Sravanti et al [22] and Shrestha et al [19]. Oruganti et al [18] observed "high genetic advance for grain yield and plant height. Moderate genetic advance was recorded by number of kernels per row (11.92%), days to maturity (11.16%) and 100-kernel weight (10.62%)".…”
Section: Estimation Of Heritability and Genetic Advancesupporting
confidence: 55%
See 4 more Smart Citations
“…High genetic advance for grain yield was also found by Sesay et al [14], Sravanti et al [22] and Shrestha et al [19]. Oruganti et al [18] observed "high genetic advance for grain yield and plant height. Moderate genetic advance was recorded by number of kernels per row (11.92%), days to maturity (11.16%) and 100-kernel weight (10.62%)".…”
Section: Estimation Of Heritability and Genetic Advancesupporting
confidence: 55%
“…High estimates of PCV and GCV was also reported for grain yield and ear height by Shrestha et al [19]. Similarly, Jilo et al [15], Mager et al [17], Rai et al [16], Oruganti et al [18], Yadav et al [20] and Thakur et al [21] were reported for grain yield. The other characters shelling percentage, days to 50%tasseling, days to 50%silking, days to maturity and number of kernel rows per ear were recorded low PCV and GCV.…”
Section: Phenotypic and Genotypic Coefficients Of Variationmentioning
confidence: 72%
See 3 more Smart Citations